Improvement of concrete performance through treatment of coarse recycled concrete aggregates with acid solutions and addition of aluminium sulphate - Valencia, Javier Andres Forero (2023)
Tese (doutorado) — Universidade de Brasília, Programa de Pós-Graduação em Estruturas e Construção Civil, Faculdade de Tecnologia, 2023.